EXCESSIVE DEFICIT PROCEDURE: PAST, PRESENT, PERFECT? - CSŰRÖS , Gabriella (International Journal of Legal and Social Order, 2022)
The Economic and Monetary Union combines a single monetary policy with decentralised economic, especially fiscal policies under the responsibility of Member States. From the Treaty of Maastricht the EU is trying to optimise the specific institutions of one-armed European economic governance – with more or less success. The excessive deficit procedure is an elementary part of the system. The study focuses on the changes and criticism of the procedure paying particular attention to public debt and the sanctions that may be imposed.